Enhancing Solar Dryer Performance with Combined Flat Plate Absorber and Parabolic Trough Collector: A Comprehensive Techno-Economic and Environmental Study - Behzad-, M (Elsevier Ltd, 2025)
In this study, the drying performance of a new solar collector was evaluated. The parabolic trough collector transfers heat to the water flow, which is then sent to the airflow through metallic spiral tubes. Techno-economic and environmental indicators were compared between single arrangement of flat-plate collector, and the combined arrangement of flat-plate and parabolic trough collectors. The results indicated that both arrangements reduced drying time by 7 h compared to direct sunlight. Additionally, the combined arrangement increased efficiency by 8 %, reduced the moisture ratio by 18 %, and enhanced the drying rate by 6 % compared to the single arrangement. The combined configuration achieves a higher ΔT, averaging 11–16 °C daily, despite lower solar intensity, compared to the 5–14 °C range observed in the single configuration. The economic analysis showed a levelized cost of heat of $0.16 USD/kWh for the combined arrangement. The environmental benefit is promising, with a reduction of 104–219 kg CO2 annually instead of burning natural gas. Utilizing such an integrated movable device should be encouraged in locations capable of exploiting solar energy while facing environmental contamination issues. © 2025 Elsevier Ltd